The impact of non performing loan on profitability of domestic licensed commercial banks in sri lanka - Brintha, P.; Arthikga, K.; Nishanthi, T. (University of Jaffna, 2016)
Non-performing loans is the single most important threat that a bank can face. It is weighted against the total portfolio of all loans and advances to assess its magnitude. Non Performing Loans have a direct impact on profitability of banks. This study also examines the impact of non-performing loan on profitability of domestic licensed commercial banks in Sri Lanka over a period of past 9 years 2006 to 2014.In this study, Nine domestic licensed commercial banks have been selected on random sample for the purpose of data analysis and Secondary data has been collected to analyze and draw conclusions and recommendations. Hypotheses are examined with help of Pearson's correlation and regression analysis. This study considers non-performing loan ratio as independent variable and return on asset and return on equity as dependent variables. Firm size is a control variable. Data was collected from domestic licensed commercial banks' annual reports, journals and websites. The result of this study has shown that non-performing loan has negative relationship with profitability of domestic licensed commercial banks. So Managers of domestic licensed Commercial banks in Sri Lanka have to work hard to enhance profitability of commercial banks and reduce occurrences of nonperforming loans.
Keywords: Commercial banks; Non performing loan; Profitability; ROA; ROE